Phellem versus xylem: genome-wide transcriptomic analysis reveals novel regulators of cork formation in cork oak. (19th December 2019) - Lopes, Susana T; Sobral, Daniel; Costa, Bruno; Perdiguero, Pedro; Chaves, Inês; Costa, Augusta; Miguel, Célia M
Abstract: Cork cambium (or phellogen) is a secondary meristem responsible for the formation of phelloderm and phellem/cork, which together compose the periderm. In Quercus suber L., the phellogen is active throughout the entire life of the tree, producing a continuous and renewable outer bark of cork. To identify specific candidate genes associated with cork cambium activity and phellem differentiation, we performed a comparative transcriptomic study of Q. suber secondary growth tissues (xylem and phellogen/phellem) using RNA-seq. The present work provides a high-resolution map of all the transcripts identified in the phellogen/phellem tissues. A total of 6013 differentially expressed genes were identified, with 2875 of the transcripts being specifically enriched during the cork formation process versus secondary xylem formation. Furthermore, cork samples originating from the original phellogen (`virgin' cork) and from a traumatic phellogen (`amadia' cork) were also compared. Our results point to a shortlist of potentially relevant candidate genes regulating phellogen activity and phellem differentiation, including novel genes involved in the suberization process, as well as genes associated to ethylene and jasmonate signaling and to meristem function. The future functional characterization of some of the identified candidate genes will help to elucidate the molecular mechanisms underlying cork cambium activity and phellem differentiation.